EURASIAN ECONOMIC UNION: IMPROVING THE LEGAL FRAMEWORK - N. E. Kotova (Финансы: теория и практика)
The paper deals with the structural elements of the legislative and regulatory framework and the law-making activities of the Eurasian Economic Union in the dynamics of institutional formation and recording of the integration process in statutory documents with account for the WTO experience. The integration process includes multiple multilateral international agreements aiming to establish a supra-national legislation as a regulator of integration processes for the benefit of the EAEU members. A subject of interest is the establishment of the law-enforcement practice as an effective tool for ensuring the planned dynamics of the integration process and compliance with agreements reached within the EAEU framework. The role of the Eurasian Economic Commission in monitoring the legislations of the EAEU member states in terms of their compliance with international treaties and the EAEU laws to avoid duplication of regulations and discard outdated rules and requirements in national legislations is discussed. Attention is paid to the role of the Eurasian Economic Court in ensuring the appropriate level of the law- enforcement practice in the Union and its members. Finally, the paper discusses the research and expert-analytical activities for the analysis of the law to identify factors affecting the export competitiveness of goods, works (services), the mechanism for dispute settlement, etc. with a purpose of making appropriate proposals concerning the legislation and its regulatory effect on the integration processes within the EAEU.